A Semantic Analysis of Grammatical Meaning in Bernadya’s Album Sialnya, Hidup Harus Tetap Berjalan - Lestari, Tri; Zain, Nurdiana; Fatmala, Siti; Firmansyah, Dody (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2025)
Semantics has various types of meanings contained within it, one of which is grammatical meaning. Grammatical meaning is a meaning that arises due to the processes of affixation (addition of affixes), reduplication (repetition), and composition (compounding). Grammatical meaning in this study is used to analyze the lyrics of songs on Bernadya's latest album titled "Sialnya, Hidup Harus Tetap Berjalan" (Unfortunately, Life Must Go On). The aim is to identify and describe the forms of grammatical meaning in the lyrics of songs that are currently viral, listened to and liked by those who are heartbroken. This research method employs a descriptive qualitative approach with the steps of directly observing and listening to Bernadya's songs, as well as analyzing the text in the lyrics of the album "Sialnya Hidup Harus Tetap Berjalan" which emphasizes in-depth meaning. The results of this study found many forms of grammatical meaning that arise due to the process of affixation, which includes verbs such as suffixes, prefixes, and confixes. Many instances were also found in the reduplication process, although not more than the affixation data, and there is only one instance of grammatical meaning through the process of composition.